Electron acceleration in intense laser–solid interactions at parallel incidence. (September 2021) - Shen, X F; Pukhov, A M; Perevalov, S E; Soloviev, A A
Abstract: Using multidimensional particle-in-cell simulations, we show that an electron beam with a huge space charge can be accelerated to high energies by irradiating the edge of a solid density target with an intense femtosecond laser pulse at parallel incidence. The process of energy gain of each electron is divided into two parts: the transverse laser field and the longitudinal field of the excited surface plasma wave (SPW). It is shown that the longitudinal field of the SPW dominates the acceleration of the major part of electrons. This process leads to generation of a highly collimated electron beam with a huge space charge.